Ecosystem goods and services in semi-arid lanscape : an examination of the relationship between ecological processes, land-use strategies and biodiversity conservation - O'Farrell, Patrick John (Plant Conservation Unit (PCU), 2024)
[page 80, 121, 137, x2; 20, 156 missing] Biodiversity loss and the disruption and degradation of ecosystems is proceeding at unprecedented rates. Conservation areas are insufficient to protect all species and there is growing recognition of the need to promote biodiversity conservation on private land, through the adoption of biodiversity-friendly land-use practices. Conservation and ecosystem function are linked to the delivery of ecosystem goods and services, which are processes and conditions of ecosystems that benefit humans and their activities. The research focus on ecosystem goods and services to date has been at global and regional scales, and there is a paucity of research at the fine scale. Benefits need to be measured and evaluated at a fine scale if land-users are to adopt best practices. The central aim of this study was to examine the relationship between commercial agricultural land-use practices and ecosystem goods and services in a biodiversity hotspot in a semi-arid area of South Africa. The approach adopted was based on the premise that to influence management activities and land-use practices it is best to first develop an understanding of what farmers perceive to be the most important ecosystem goods and services and how they manage their landscapes according to these perceptions. Farmers recognise and value a broad range of ecosystem goods and services that they incorporate into their farming practices, and their management framework is structured according to these in an attempt to optimise production. Ecosystem goods and services are perceived according to landscape heterogeneity which provides temporal and spatial opportunities for their exploitation. An exploration of the effects of land-use practices on identified ecosystem goods and services showed these to be highly dependent on the incorporation of natural vegetation and the maintenance of key ecological processes. Natural vegetation is essential for the provision of goods and services related to grazing and livestock production, with different vegetation types providing different goods and services. The maintenance of the service provided by an abundance of small mammals as an alternative source of prey to livestock for medium-sized predators, was demonstrated to be highly dependent upon landscape and vegetation structure, with 82% of all mammals trapped in the most structurally diverse vegetation type, vegetation clearance resulted in a seven fold decrease in small mammal abundance. A detailed examination of rainfall infiltration and erosion in natural, transformed and managed transformed vegetation showed there to be greater infiltration, less run-off, wind speeds reduced four fold, and eight times less soil lost to wind erosion in natural vegetation compared with transformed areas. However, in managed transformed areas, rainfall infiltration was greater than in natural and transformed areas. An examination of the key ecological processes maintaining soil health showed a decline in 1 soil invertebrate activity with increasing distance from natural vegetation remnants. However, under managed transformed conditions earthworm populations were three times greater than in natural vegetation remnants and this may account for greater infiltration rates measured here. An exploration of the potential to develop horticultural products from the species in the area, demonstrated the importance of the retention of natural vegetation as repositories of future-use options. In comparing farmers' perceptions, with analysed ecosystem goods and services, their perceptions were demonstrated to be generally accurate in their identification of ecosystem goods and services. While their perceptions may be correct, the value farmers place on a particular service is often not sufficient to influence fanning practice. Farmers appear to misjudge the degree of magnitude that management effects have on the delivery of ecosystem goods and services. Despite farmers perceiving the general concept of future-use options, they do not perceive the repository potential of their own remnant patches of natural vegetation for ecosystem goods. The broader objective of this thesis has been to consider the role that an understanding of ecosystem goods and services can play in promoting biodiversity conservation on private agricultural land. While scientists grapple with the conceptual issue of how diversity links to ecosystem processes, whether all species are important, and finally how these may benefit humans, farmers work at a mdre intuitive level trying to achieve benefits for themselves based on their experiences and perceptions, which influence land strategies. As a result, understanding farmers' perceptions and testing some of their assumptions can provide a basis for illustrating the links between biodiversity and goods and services at a farm level and in this way offer opportunities for conservation on private land.